What Tudors and Stuarts Did For Us - Hart-Davis, Adam (London Boxtree, 2002)
Tudor and Stuart England saw the most dramatic shifts in thinking and innovation since the Romans. Adam Hart-Davis illuminates on the innovations of the period and shows how these Tudor and Stuart advancements have changed our world.
Include Index and Illustration
Keywords: Great Britain -- Inventions